Peritoneal Reflections and Ligamentous Anatomy of the Abdomen: A Systematic Review with Surgical Correlation: Peritoneal Reflections and Ligamentous Anatomy of the Abdomen - Akhtar, Naz; Javed, Iqra; Ghulam, Bushra; Jabbar, Naila; Khan, Sumta; Shabeer, Khurram (Pakistan Journal of Health Sciences, 2026)
Peritoneal reflections and fibrous abdominal ligaments serve as anatomical scaffolds that guide surgical dissection, facilitate organ mobility, and influence the spread of disease. Recent advances in imaging and minimally invasive surgery have revealed greater anatomical variability than previously recognized, highlighting the need for an updated synthesis. Objectives: To systematically review recent anatomical, imaging-based, and intraoperative studies describing peritoneal reflections and abdominal ligaments, and to evaluate their surgical relevance across major abdominal specialties. Methods: This systematic review was conducted in accordance with PRISMA 2020 guidelines. PubMed, Scopus, Web of Science, and Google Scholar were searched for human studies published between 2018 and 2024. Original cadaveric, radiologic, and surgical studies were eligible for inclusion. Data screening, extraction, and quality appraisal were independently performed by two reviewers using the Joanna Briggs Institute (JBI) tools. Results: A total of 15 studies met the inclusion criteria. Most studies reported structural variation in pelvic peritoneal pockets, hepatogastric folds, the falciform and round ligaments, and the anterior peritoneal reflection. Imaging-based investigations demonstrated patient-specific variation in peritoneal surface area. Intraoperative studies highlighted the impact of these variations on dissection planes, reconstruction feasibility, surgical exposure, and oncologic decision-making. Conclusions: Anatomical variability of peritoneal reflections and abdominal ligaments significantly influences hepatobiliary, pelvic, hernia, and colorectal surgery. Recognition of these variations improves surgical safety and supports individualized operative planning.